PROTEKSI INDONESIA DI SEKTOR HORTIKULTURA DALAM LIBERALISASI PERDAGANGAN WTO TAHUN 2011 – 2013 - Ryan Fadhillah; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Indonesia has always hummed as the rich agricultural country varieties of plants including a wide range of fruit varieties. Especially for horticulture sector, in trade liberalization of WTO. Indonesia’s trying to protect horticulture national and pressing horticulture ekspor. As the rich agricultural country, indonesia’s trying to do self-sufficient horticulture sector.Protectionism theory that is used to see how Indonesia pressing horticulture import sector overflow as forbidden substance in WTO forum itself. So that, Indonesia used “Special and Differential Treatment Right” which is a special right in WTO Forum for developing countries on getting used to integration and trade liberalizationIndonesia’s protectionism in “Special and Differential Treatment Right” affected its horticulture sector, especially the export and import sector. Indonesia successfully increased its horticulture export, almost in all fruit sector in 2012 and also pressing the import sector even though it didn’t achieve maximal gains.Keywords: Indonesia’s Agriculture, Horticulture, , Protectionism